Towards an agency-oriented model of congregational vitality: - C.A.M. Hermans (Acta Theologica, 2024)
The author defines ‘congregational vitality’ as a disposition of the members of the congregation, who act in a role within the social system of the congregation. He connects this agency-related perspective with a structural-functionalist perspective on local churches after the agentic turn. Functions are dynamic processes of a system that are ‘needs’ in terms of maintenance of stability or production of change Two functions are necessary for survival and continued operation (adaptation and goal attainment) and two functions are related to the quality and internal regulation of cultural patterns and values (integration and pattern maintenance). Contextual changes, notably ethnic exclusivity and social justice, affect the congregational vitality of the actors. This loss of vitality deepens the crisis of congregations. The author concludes with two evidenceinformed programmes which can transform this loss of vitality related to the challenges that congregations face.